Religija kaip pirmoji filosofija = Religious as a first philosophy accordering to Levinas - Čepulis, Nerijus (Religija ir kultūra, 2007)
The term metaphysics is ascribed to Aristotle, although it does not appear in his own texts. Historically it was introduced while sorting Aristotle’s works. In Greek t" met" t" fusikmeans that which follows after physics. The author of the Metaphysics groups theoretical philosophy into three branches: mathematics, physics and theology. Theoretical sciences are more elevated than the other sciences, while the last one of the three is more elevated than the other two. If there were no substance that would superseed the nature, then physics would be the first among the sciences. If, however, there is sume unchanging substance, then the science of it undoubtedly will rise above all the other and will be called the first philosophy (filosof%a pr_th). Precisely this science has to look at the being as such,kaθ ’aÑtÊ in Greek.According to Levinas, the metaphtysical thinking seeks to think the being as radically separated, solitary and single (kaθ ’aÑtÊ), and this requires a special attention to the absolute exteriority and the other that refuses to be totalized. The metaphysical movement is transcendental, because as a desire for the goodness and generosity does not overcome and does not seek to overcome the primordial distance from the other. The metaphysical relation to the other for Levinas is a social one. The absolutely other first of all is the Other - the other person that is not bound with me neither by appropriation, nor by term, nor by any general level. Between us there is a distance separating the same and the other that is not to be covered. The possibility or the way to relate in this distance without abolishing or overcoming it is language. In the relation of the same to the absolutely other beyond the totality Levinas finds the essence of religion. Here religion coincides or at least closely relates to metaphysics. From this follows that religion can take the place of the first philosophy, without forgetting that the essence of both metaphysics and religion is the fundamental sociability.